Análisis de estrategias de eficiencia energética para dispositivos móviles, basado en el concepto de green it - Fernández Sangucho, Carlos Alberto (2016)
The smartphones advanced features and functionalities have come to largely displace conventional mobile phone. For this reason, there is a growing demand for smart phones all over the world. However, one of the problems faced by these devices is to ensure autonomy in battery life, regardless of their operating system and applications used. With reference to the previous, there are different batteries on the market, so the comparison is complex regarding its duration. Nevertheless, many of these devices handle different configurations for energy saving, but it is still insufficient. It is necessary to establish other mechanisms to optimize their use. Based on the considerations described, it seeks to identify the hardware components that drain the battery of a Smartphone. To achieve this purpose, it is a methodology to measure power consumption on a mobile device with Android operating system, taking into account the benefits offered by the open source and application development environment arises.